Diseño de la documentación para el sistema de gestión de calidad de acuerdo con el estándar NTC ISO9001:2015 para la empresa Fundasalud (2021)
The search for competitiveness and productivity of companies has been the oldest way to guarantee their sustainability over time. For this reason, organizational sciences have carried out different contributions that adjust to different factors and trends of the client and the markets. The present project obeys to the problem of low productivity and different adverse situations faced by the company due to lack of control of processes and resources, leading to the need to design the documentation of the quality management system from the fundamentals of the NTC ISO 9001:2015. The project consists of a descriptive approach research in which the level of compliance with the standard was established as an initial diagnosis, subsequently and guided by the standard, risks and opportunities were identified, the characterization of the processes and the establishment of the documents required for the system were carried out. Once the documentation was designed, a brief study of the cost-benefit of the project for the company was carried out.